PENINGKATAN KEMAMPUAN OPERASI HITUNG BILANGAN CACAH MELALUI PEMBELAJARAN MATEMATIKA REALISTIK DI KELAS IV - Chamidah, Zidni; Prasetyo, Aris Kukuh; Setiani, Kesia Indah (JS (JURNAL SEKOLAH), 2023)
Abstract: Improving the Capability of Whole Number Counting Operations Through Realistic Mathematics Learning in Class IV SD Negeri Blotongan 02. This research aims to improve the ability to calculate whole number operations by applying realistic mathematics learning through Collaborative Classroom Action Research (PTKK). The research was conducted using the Kemmis and MC Taggart model which consists of the planning stage, the implementation/action stage, the observation stage, and the reflection stage. The subjects of this research were 18 students in class IV A at SD Negeri Blotongan 02, Salatiga City. Data was collected using observation, test and documentation techniques. Data analysis uses descriptive quantitative data analysis techniques. The indicator of research success is the completeness of learning outcomes, 75% of the number of students reaching the KKM (75). The research results showed that only 5 students (28%) completed the pre-cycle learning results. Cycle I began to increase with the learning outcomes of 8 students (44%) being complete. The increase in learning outcomes achieved indicators of research success in cycle II, namely 14 students (78%) completed. Based on this, it is concluded that realistic mathematics learning can improve the ability to calculate whole number operations as demonstrated by increasing the completeness of students' learning outcomes. Keyword: Learning Outcomes, Realistic Mathematics Learning, Mathematics Abstrak: Peningkatan Kemampuan Operasi Hitung Bilangan Cacah Melalui Pembelajaran Matematika Realistik di Kelas IV SD Negeri Blotongan 02. Penelitian ini bertujuan untuk meningkatkan kemampuan operasi hitung bilangan cacah dengan penerapan pembelajaran matematika realistik melalui Penelitian Tindakan Kelas Kolaboratif (PTKK). Penelitian dilakukan menggunakan model Kemmis dan MC Taggart yang terdiri dari tahap perencanaan (planning), tahap pelaksanaan/tindakan (action), tahap pengamatan (observation), dan tahap refleksi (reflection). Subjek penelitian ini adalah 18 peserta didik kelas IV A SD Negeri Blotongan 02 Kota Salatiga. Data dikumpulkan menggunakan teknik observasi, tes, dan dokumentasi. Analisis data menggunakan teknik analisis data kuantitatif deskriptif. Indikator keberhasilan penelitian yaitu ketuntasan hasil belajar 75% jumlah peserta didik mencapai KKM (75). Hasil penelitian menunjukkan hasil belajar pra siklus hanya 5 peserta didik (28%) tuntas. Siklus I mulai adanya peningkatan dengan hasil belajar 8 peserta didik (44%) tuntas. Peningkatan hasil belajar mencapai indikator keberhasilan penelitian pada siklus II yaitu 14 peserta didik (78%) tuntas. Berdasarkan hal tersebut, disimpulkan bahwa pembelajaran matematika realistik dapat meningkatkan kemampuan operasi hitung bilangan cacah yang ditunjukkan melalui peningkatan ketuntasan hasil belajar peserta didik. Kata kunci: Hasil Belajar, Pembelajaran Matematika Realistik, Matematika